Happiness (Harvard Business Review Press, 2017)
Happiness: What is the nature of human happiness, and how do we achieve it in the course of our professional lives? And is it even worth pursuing? This book explores answers to these questions by presenting research into how to measure happiness, frameworks for personal behaviors, management techniques that build happiness in the workplace--and warnings that highlight where the happiness hype has been overblown